Sosialisasi pencegahan pernikahan dini sebagai upaya penguatan pendidikan dan kesadaran hukum siswa SMAN 1 Sajira - Saputra, Desma Yuliadi; Mardhiyah Lestari; Reni Apriani; Dina Puspita Sari; Syifaul Inayah; Lulu Annazmi; Dede Putri (Penamas: Journal of Community Service, 2025)
Child marriage remains a concerning phenomenon in Indonesia, including in Lebak Regency, with serious implications for adolescents' health, education, and socioeconomic conditions, particularly for girls. Multifaceted causes, including low educational attainment, poor family economic conditions, social and cultural pressures, and limited legal awareness, drive this practice. Similar situations are also found among students, including those at SMAN 1 Sajira. In response, the Student Community Service Program (KKM) Group 63 conducted a community engagement activity in the form of a socialization program on preventing child marriage, under the theme "Prevent Early Marriage, Create a Bright Future through Education." The activity involved speakers from legal and educational perspectives and was conducted interactively through presentations and discussions. The results indicated an increase in students' knowledge and awareness of the risks of child marriage, the importance of continuing education, and the understanding of applicable legal protections. This program is expected not only to benefit students of SMAN 1 Sajira but also to serve as an educational model that can be replicated in other schools to support efforts to prevent child marriage in Lebak Regency and beyond.